(untitled) (Research, Society and Development, 2021)
Oxi-reduction can be considered in chemistry teaching a difficult content to be worked on and assimilated by teachers and students, due to its abstract character and the language used, highlighting the need for actions that facilitate the assimilation of concepts and consider the previous knowledge of the students in order to facilitate meaningful learning. Thus, the work aimed to identify the students’ prior knowledge from activities that used the corrosion theme as a previous organizer with a view to meaningful learning. The research was based on a qualitative approach and participant research, with data collected through a Potentially Significant Teaching Unit (UEPS) in a Public School in the city of Manaus, with seventeen second-year high school students, The data collection was for questionnaire, conversation circle and text production. Data were evaluated by content analysis. In the results, previous knowledge not initially evidenced were chemical transformations, chemical reactions and redox reactions and the factors that affect the reactions, however, using the previous organizer it was possible to access implicit knowledge about the factors that affect redox reactions such as water and oxygen, and relational perceptions of the theme with daily life in terms of health, environment and socioeconomic factors. The use of the corrosion theme contributed significantly to initiate the oxidation-reduction teaching-learning process, allowing the construction of a relation between the dayle and the scientific, giving meaning to the new information to be anchored.